2019
DOI: 10.3390/antiox8110535
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and IUGR Pregnancies: Effects of Maternal Hydroxytyrosol Supplementation on Postnatal Growth, Metabolism and Body Composition of the Offspring

Abstract: Maternal supplementation with the polyphenol hydroxytyrosol in a swine model of intrauterine growth restriction (IUGR) improves the fetal oxidative status, decreases the appearance of low birth-weight neonates and favors growth during early postnatal stages (lactation). The current study aimed to determine whether hydroxytyrosol supplementation can also improve developmental patterns, metabolic traits, and body composition of the offspring during later postnatal stages (from weaning to adulthood). A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The assessment of piglets’ features during late postnatal stages (juvenile development) showed higher values of phenotypic characteristics (body-weight, back-fat depth and loin diameter) in the pigs from treated sows, in agreement with previous studies on swine developmental patterns [ 53 , 54 , 55 ] and, specifically, in studies focused on maternal supplementation with only hydroxytyrosol [ 5 , 6 ] or only n3 fatty acids [ 41 , 56 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The assessment of piglets’ features during late postnatal stages (juvenile development) showed higher values of phenotypic characteristics (body-weight, back-fat depth and loin diameter) in the pigs from treated sows, in agreement with previous studies on swine developmental patterns [ 53 , 54 , 55 ] and, specifically, in studies focused on maternal supplementation with only hydroxytyrosol [ 5 , 6 ] or only n3 fatty acids [ 41 , 56 ].…”
Section: Discussionsupporting
confidence: 89%
“…Hydroxytyrosol is a polyphenol present in olive leaves and fruits with even higher antioxidant capacity than vitamin E [ 2 ]. Maternal supplementation during pregnancy improves oxidative and metabolic status of IUGR fetuses [ 3 , 4 ] and therefore incidence of LBW neonates and postnatal development of piglets [ 5 , 6 ]. Specifically, hydroxytyrosol diminishes lipid peroxidation and increases the fetal availability of omega-3 and omega-6 polyunsaturated fatty acids (n3 and n6 PUFAs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies in a different species, the pig, have shown that maternal supplementation with antioxidant compounds (polyphenols in this case), improves antioxidant status of the fetuses [30] and body weight of the neonates [31]. Afterwards, developmental patterns were positively affected by maternal supplementation independently of birth weight since, comparing individuals with similar weight at birth and weaning, piglets from supplemented sows reached higher average daily weight gain and, therefore, higher body weight and corpulence than their control counterparts [32].…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we aimed to determine the effects of a maternal supplementation with n-3 PUFA and hydroxytyrosol, from day 35 of gestation onwards, on body composition and metabolic and oxidative stress status in sows and their progeny using an animal model that has previously shown to increase the appearance of IUGR offspring [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxytyrosol has also been shown to diminish lipid peroxidation in swine fetuses, increasing their availability of omega-3 and omega-6 polyunsaturated fatty acids (n-3 and n-6 PUFA) [4]. Our group has previously shown the usefulness of this compound to counteract the appearance of intrauterine growth restriction (IUGR) and, therefore, to diminish the incidence of low birth weight (LBW) neonates and to favor the postnatal development of the piglets [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%